The Influence of Application of Portfolio-Based Learning Model on Student Learning Outcomes in History Class XI - Nur Jayanto; Shamal Kaveh; Gleen A Davies (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research was conducted with the aim of knowing the effect of applying a portfolio-based learning model on student learning outcomes in history class XISMAN Negeri 1 Kembang in the 2012-2013 academic year. Methodology: This type of research is experimental research. The experimental design used is the Pre test-Post test. The population in this study were all students of class XI IPS at SMA N 1 Kembang in the academic year 2012/2013, totaling 177 students. Sampling was carried out using random sampling so that researchers got XIIPS2 class as the experimental class and XIPS1 class as the control class. Main Findings: From the results of data processing, it can be concluded that the contribution of the application of portfolio-based learning models to history learning outcomes is 26.11%, so the effect of applying portfolio-based learning models to history learning outcomes can be said to be significant. Novelty/Originality of this study: This research has an update by measuring the effect of implementing a portfolio-based learning model on student learning outcomes in history subjects. With limited research samples, namely students of class XI SMA Negeri 1 Kembang in the 2012-2013 academic year.